Clinical Management of Dens Invaginatus Type 3: A Case Report - Elham Shadmehr; Ali Reza Farhad (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2011)
ABSTRACT: Dens invagination (DI) is a developmental abnormality of teeth which frequently results in a complex internal anatomy of the root canal system. DI type 3 is an anomaly characterized by infolding of enamel and dentin extending into the root apex. This may present difficulties when forming a diagnosis and treatment plan. Many treatment modalities have been presented in case reports for DI type 3, but there is insufficient evidence to recommend a therapy. This case report presents the successful non surgical root canal treatment of a maxillary canine with an open apex DI type 3, necrotic pulp, and an associated large periradicular lesion.